Analisis Penggunaan Media Pembelajaran SBDP Di Kelas V SD GKST Talabosa - Yubelium Putra Topei, yubel; Ratna Lagandesa, yun; Bim M. Gagaramusu, Yusdin; Pahriadi, Pahriadi (JURNAL DIKDAS, 2023)
Instructional media plays an important role as a tool for conveying messages from teachers to students, particularly in delivering curriculum-based material. The use of media in the learning process can stimulate students' thoughts, emotions, attention, and motivation, thereby promoting a more effective learning experience. Media also assists teachers in conveying messages, especially those that are difficult to express through words alone. This study utilized a questionnaire method with multiple-choice and forced-choice types (such as yes–no or agree–disagree), selected for their ease of completion and minimal cognitive load for respondents. An interview technique was also employed, specifically with the principal of SD GKST Talabosa, to understand the implementation of media use in SBdP (Arts, Culture, and Craft) learning. Additionally, questionnaires were distributed to fifth-grade students to gather data on their perceptions and experiences with the use of instructional media. The collected data were presented in tables and descriptive explanations. The results indicated that most students felt their teacher frequently used media in SBdP lessons. A total of 90% of respondents stated that the teacher often used instructional media, while 10% stated it was used very frequently. No respondents reported that the teacher rarely or never used media. Therefore, it can be concluded that the use of instructional media in SBdP learning for fifth-grade students at SD GKST Talabosa is considered fairly good, although some inhibiting factors still exist in its implementation.